Pengaruh Orientasi Pasar, Orientasi Kewirausahaan dan Kemampuan Pemasaran terhadap Kinerja Bisnis UMKM di Kecamatan Balung - Siwi Kartikasari; Haris Hermawan; Yohanes Wibowo (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
MSMEs are one of the main pillars of the Indonesian economy, including in Balung District, Jember Regency, which in recent years has shown growth in the number of business units and the level of digital technology adoption. However, the increase in business quantity and the digitalization process has not been fully accompanied by optimal improvements in business performance. Most MSMEs in Balung still face various obstacles, particularly in understanding market dynamics, demonstrating an adaptive entrepreneurial attitude, and managing their businesses with effective strategies. This study aims to analyze the influence of market orientation, entrepreneurial orientation, and marketing capabilities on MSME business performance in Balung District. The study used a quantitative approach with a survey method. The study population was all 7,304 MSMEs in Balung District, while the research sample was determined at 100 respondents through a purposive sampling technique. Data were collected using a questionnaire and analyzed using multiple linear regression. The results showed that market orientation and entrepreneurial orientation have a positive and significant effect on MSME business performance. Meanwhile, marketing capabilities, although positive, were not statistically significant. These findings indicate that the ability to understand consumer needs, be innovative, proactive, and take risks are more crucial factors in improving business performance than purely technical marketing skills. The implication of this research is the need for strategies to strengthen market orientation and entrepreneurship through comprehensive coaching, training, and facilitating access to market information, product innovation, and business management. This research is also expected to serve as a reference in policy formulation and further research on MSME performance in the local context.